Elementy wspólnego pisania na zajęciach pisania akademickiego – badanie pilotażowe - Marzec-Stawiarska, Małgorzata (Neofilolog, 2012)
The article discusses the issue of collaborative writing during classes of academic writing for advanced students of English as a foreign language. It describes a research project in which the influence of collaborative planning on the quality of written discourse was analysed. The research found that essays based on the plan constructed by students in pairs were better in terms of organisation, linguistic variety, content and accuracy than essays written by these participants individually. Moreover, the questionnaires written by the participants revealed their positive attitude to collaborative essay planning.